Synthesis of New Quinoline-Piperonal Hybrids as Potential Drugs against Alzheimer's Disease - de Oliveira C Brum, Juliana; Neto, Denise Cristian F; de Almeida, Joyce Sobreiro F D; Lima, Josélia Alencar; Kuca, Kamil; França, Tanos Celmar C; Figueroa-Villar, José D (International journal of molecular sciences, 2019)
Six quinoline-piperonal hybrids were synthesized and evaluated as potential drugs against Alzheimer's disease (AD). Theoretical analysis of the pharmacokinetic and toxicological properties of the compounds suggest that they present good oral bio-availability and are also capable of penetrating the blood-brain barrier, qualifying as leads for new drugs against AD. Evaluation of their inhibitory capacity against acetyl- and butyrilcholinesterases (AChE and BChE) through Ellmann's test showed that three compounds present promising results with one of them being capable of inhibiting both enzymes. Further docking studies of the six compounds synthesized helped to elucidate the main interactions that may be responsible for the inhibitory activities observed.
Keywords: kinetika; benzodioxoly; Quinolines; simulace molekulového dockingu; cholinesterasové inhibitory; Magnetic Resonance Spectroscopy; Chemistry Techniques, Synthetic; magnetická rezonanční spektroskopie; Cholinesterase Inhibitors; benzaldehydy; Alzheimer Disease; Molecular Dynamics Simulation; Molecular Docking Simulation; Benzaldehydes; vztahy mezi strukturou a aktivitou; Humans; techniky syntetické chemie; Kinetics; simulace molekulární dynamiky; molekulární struktura; Alzheimerova nemoc; Benzodioxoles; Structure-Activity Relationship; chinoliny; lidé; Molecular Structure